Gold Price and Exchange Rate Volatility: Effects of Economic Sanctions - Mashayekhi, Bita; Sadr Ara, Mehrdad; Jafari, Ashraf (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The gold market has recently attracted much attention and gold prices have fluctuated over the past few years. Therefore, the aim of this study is investigate and analyze the trend of gold prices over the past five years in Iran. The importance of this topic is coming from uncertainty and volatility of the gold market, gold excitement and lack of a correct analysis of the market trends with reference to the probable factors which affect the gold price. The studys period refers to the ended five-year in December 2012. This research from methodological point of view is a descriptive-perspective analysis that examines the influence of variables such as the gold price on the market, the official exchange rate and non-official rate on the Irans market, the price of Brent crude oil, the global rate per ounce gold and foreign economic sanction. Vector auto regression model is used to analyze the results of the study. The results indicate that gold price is affected from exchange rates fluctuations and gold global rate, it is also noteworthy to mention that the most important factors affecting the recent volatility in the Irans gold market and the exchange rate is the economic sanctions which have been imposed against Iran.